Correspondence of genotypes of sporadic Yersinia enterocolitica bioserotype 4/O:3 strains from human and porcine sources. - Fredriksson-Ahomaa, M. (Cambridge University Press, 2001)
The sources and transmission routes of sporadic Yersinia enterocolitica bioserotype 4/O:3 infections in Finland were studied. A total of 212 human strains were compared with 334 non-human strains, including 163 strains from pig slaughterhouses, 164 strains from retail outlets and 7 strains from pet animals. All strains were characterized using pulsed-field gel electrophoresis (PFGE) with NotI enzyme. When the 194 human and 287 non-human strains of 22 identical NotI profiles were further characterized with ApaI and XhoI enzymes, 126 genotypes (DI = 094) were distinguished. Of all 212 human strains, 80% were genetically indistinguishable from the strains found in samples of pig origin when characterized with the three enzymes. A major contamination source of sporadic Y. enterocolitica 4/O:3 infections was revealed to be edible pig offal: 71% of the human strains were indistinguishable from the strains isolated from tongues, livers, kidneys and hearts of pigs. These results reveal that in Finland contaminated pig offal is an important vehiclein the transmission of Y. enterocolitica bioserotype 4/O:3 from slaughterhouses to humans.